Рак печінки: мікроскопічні і імуногістохімічні диференційні та прогностичні характеристики - Зубко, Марія Дмитрівна; Zubko, Marija Dmytrivna (Запорізький державний медичний університет, 2016)
У дисертації за результатами комплексного патоморфологічного дослідження показано, що ГЦР та ХЦР притаманна значна варіабельність мікроструктури з наявністю декількох гістоархітектонічних патернів. Виявлено, що ГЦР характеризується експресією HepРar-1 і AFP, HBsAg і HBcAg, та варіабельною експресією СК8, СК7, СК19 і СК20. Внутрішньопечінковий ХЦР характеризується експресією СК7, AFP, СК20, HBsAg і HBcAg, відсутністю експресії HepPar-1, а також експресією муцинозних маркерів в залозисто-ацинарному патерні. Показано, що ГЦР і внутрішньопечінковий ХЦР відрізняються високою проліферативною та низькою апоптотичною активністю, а також високим інвазивним потенціалом. ГЦР і ХЦР також характеризуються достовірною втратою експресії клітинами Е-кадгеріну і зростанням аномальної експресії β-катеніну. Прогностично несприятливими параметрами ГЦР і ХЦР є достовірне зростання рівня експресії клітинами Кі-67, р53, ММР-9 і β-катеніну на тлі низької експресії каспази-3-, ТІМР-1 і Е-кадгерину. Визначено, що на відміну від ГЦР, метастази інших злоякісних пухлин солідно-трабекулярної мікроструктури в печінці характеризуються відсутністю експресії гепатоцитарних маркерів і можуть бути ідентифіковані за своїм характерним ІГХ профілем. Диференційний діагноз ХЦР та метастазів в печінку ПРПЗ, аденокарциноми шлунка та колоректального раку здійснюється або при паралельному патоморфологічному дослідженні трепанобіоптату підшлункової залози, або з урахуванням клініко-інструментальних досліджень шлунка, підшлункової залози, товстої кишки. In the current dissertation based on the results of the pathomorphological, immunohistochemical and morphometrical studies, the vast microstructure variability of HCC and CCC alongside with their several hystoarchitectonic patterns is being demonstrated. HCC is characterized by trabecular, basal cellular and acinal microscopic patterns; fibrous, cirrhotic, scirrhous variants of tumor, the valuable expression level of HepPar-1, AFP, HBsAg and HBcAg, and also the variable expression of CK8, CK7, CK19 and CK20. There is a minor correlation between the tumor cell's expression of AFP and HepPar-1. HepРar-1+ and AFP+ cells occupy correspondingly 49,35±25,45% and 37,25±5,47% of the standard HCC shear section. The HCC's typical immunophenotype is HepPar 1+ | AFP+ | СК7+/– | СК8+ | СК19+/– | СК20+/– | СА125– | СА19-9+/– | CDX2– | MUC1– | MUC5АС–. Intrahepatic CCC is being characterized by the presence of the tubular, basal cellular and glandular-acinal patterns and the scirrhous variant of the tumor, the expression of CK7, AFP, CK20, HBsAg and HBcAg and the expression of the mucinous markers in the glandular-acinal pattern. CK7, CK20 and AFP immunopositive cells occupy correspondingly 43,55±9,93%, 50,28±16,35% and 17,25±9,67% of the standard CCC shear section. The CCC's typical immunophenotype is СК7+ | СК8+/– | СК19+ | СК20+/– | СА125+ | СА19-9+ | CDX2+/– | MUC1+ | MUC5АС+ | AFP+/– | HepPar-1–. HCC and intrahepatic CCC are being characterized by means of a high proliferative activity and a minor level of apoptosis. Hyperexpression and high nuclear expression p53 of the tumor cells is being revealed in 83,64% of HCC cases and in 61,54% of CCC cases. On the background of the low caspase-3 expression – in 47,28% of HCC cases and in 48,72% of CCC cases. It is for sure, that both HCC and CCC are being characterized by the high invasive potential. There is the expression of MMP-9 in the cytoplasm being observed in 92,73% cases of HCC and in 89,74% cases of CCC, which occupy more than the half of tumor's standard shear section, while the TIMP-1+ cells occupy only 21,94±6,27% and 33,05±13,85% tumor's standard shear section. There is the strong indirect connection between the high level of cellular expression of MMP-9 and the low level of the TIMP-1 expression in both variant of cancer. Both HCC and CCC are being characterized by statistically significant loss of the cellular expression of E-cadherine alongside with the growth of nuclear and cytoplasmic β-catenin. Prognostic unfavorable parameter of both HCC and CCC is the statistically significant growth of the cellular expression of Ki-65, p53, MMP-9 and β-catenin by immunopositive cells on the background of low expression of caspase-3, TIMP-1, E-cadherine and the overall small area of the corresponding immunopositive cells, which results into invasive growth of tumor and size increase more than 5 cm. Unlike HCC's ones, the liver metastases from malignant tumors of solid-trabecular microstructure are being described by the absence of HepPar-1, AFP expression and can be identified with the help of unique IHC profile. The differential diagnosis of HCC liver's trepan-biopsy material and liver metastases of duct pancreas carcinoma, gastric adenocarcinoma and collateral carcinoma of tubular and glandular-acinal structure is possible by means of pathomorphological studying the parallel liver's tumor trepan-biopsy material, or taking into account the gastroscopy and colonoscopy data; CT of stomach, pancreas and colon.
Keywords: гепатоцелюлярний рак; холангіоцелюлярний рак; метастази; морфометрія; імуногістохімія; гепатоцеллюлярный рак; холангиоцеллюлярный рак; метастазы; морфометрия; иммуногистохимия; hepatocellular cancer; cholangiocellular cancer; metastasis; morphometry; immunohistochemistry